Costas Gaganakis, Θουκυδίδης ή Ευσέβιος; Προτεσταντική ιστοριογραφία στη Γαλλία των θρησκευτικών πολέμων (1560-1600) [Thucydides or Eusebius? Protestant historiography in France during the Religious Wars, 1560-1600] - Kokkinos, George (Historein, 2018)
Costas Gaganakis. Θουκυδίδης ή Ευσέβιος; Προτεσταντική ιστοριογραφία στη Γαλλία των θρησκευτικών πολέμων (1560-1600) [Thucydides or Eusebius? Protestant historiography in France during the Religious Wars, 1560-1600]. Athens: Polis, 2016. 172 pp